2017
DOI: 10.1002/adfm.201702784
|View full text |Cite
|
Sign up to set email alerts
|

Switching Light Transmittance by Responsive Organometallic Poly(ionic liquid)s: Control by Cross Talk of Thermal and Redox Stimuli

Abstract: A novel organometallic poly(ionic liquid) with both redox-and thermoresponsive properties is synthesized from a poly(ferrocenylsilane) (PFS) via a one-step Strecker sulfite alkylation reaction by using tetraalkylphosphonium sulfite as an effective and versatile nucleophile. This dual-responsive polymer is composed of a PFS backbone and quaternary phosphonium sulfonate side groups and exhibits a concentration-dependent lower critical solution temperature (LCST)-type phase transition in aqueous solution. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 49 publications
0
33
0
Order By: Relevance
“…122 In addition to the aforementioned applications, PILs can synergistically work with functional metal sites to develop ''smart'' hybrids or devices. [123][124][125][126][127][128][129] By incorporating a redoxactive metal site into a polyferrocenylsilane derivative (PFS-SO 3 ), Vancso and coworkers developed organometallic PFS-PIL…”
Section: Pil-metal Salt Compositesmentioning
confidence: 99%
“…122 In addition to the aforementioned applications, PILs can synergistically work with functional metal sites to develop ''smart'' hybrids or devices. [123][124][125][126][127][128][129] By incorporating a redoxactive metal site into a polyferrocenylsilane derivative (PFS-SO 3 ), Vancso and coworkers developed organometallic PFS-PIL…”
Section: Pil-metal Salt Compositesmentioning
confidence: 99%
“…[119].Copyright 2017, Wiley. was described by Zhang et al [121] This novel poly(ionic liquid) revealed aL CST-type phase transition in water by oxidizing with iron(III)chloride. The temperature-induced phase transition could be used for controlled switching of light transmittance through a" smart window" by the two individually applied external triggers (Figure 7).…”
Section: Opticalapplications For Metallopolymersmentioning
confidence: 88%
“…[120].Copyright 2017, Royal SocietyofC hemistry. [121] Reproduced with permission from Ref. [121].C opyright 2017, Wiley.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Using metallopolymers as precursors to metal nanoparticles (NPs) is key to some of these applications and this may be achieved by either radiation or thermal treatment. 7,8,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Polyferrocenylsilanes (PFSs) are a wellknown class of metallopolymers, [33][34][35][36][37] which contain both Fe and Si in the main chain. Due to the presence of these elements, these materials possess useful characteristics, such as high resistance to oxygen plasma etching and redox activity.…”
Section: Introductionmentioning
confidence: 99%